Impact of using Islamic microfinance products on Mauritanian’ income: evidence from PROCAPEC- Nouakchott - Maouloud, Vatimetou Mokhtar; Kassim, Salina; Othman, Anwar Hasan Abdullah (2020)
This study attempts to examine the impact of using Islamic microfinance products on the Mauritanian microentrepreneurs’ income level. The study is purely quantitative, and it uses cross-sectional design data which was gathered through a questionnaire from a sample of 381 beneficiaries of an Islamic microfinance institution (PROCAPEC). It uses Structural Equation Modeling (SEM) to determine the effectiveness of using Islamic microfinance products on the beneficiaries' income as well as to test the moderator effect of gender on the relationship in the model. The research found out that the use of Islamic microfinance products has increased the beneficiaries’ income; however, gender has no moderator effect on the relationship between the usage of Islamic microfinance products and income level. These findings are useful for the policymakers and managers of Islamic microfinance to consider the factors increasing the usage of Islamic microfinance products to reduce poverty in the country. This is study is among the pioneer in the field of Islamic microfinance in Mauritanian due to the scarcity of studies in the geographical context.